Lower extremity regional anesthesia: essentials of our current understanding. Issue 2 (11th January 2019) - Tran, De Q; Salinas, Francis V; Benzon, Honorio T; Neal, Joseph M
Abstract : The advent of ultrasound guidance has led to a renewed interest in regional anesthesia of the lower limb. In keeping with the American Society of Regional Anesthesia and Pain Medicine's ongoing commitment to provide intensive evidence-based education, this article presents a complete update of the 2005 comprehensive review on lower extremity peripheral nerve blocks. The current review article strives to (1) summarize the pertinent anatomy of the lumbar and sacral plexuses, (2) discuss the optimal approaches and techniques for lower limb regional anesthesia, (3) present evidence to guide the selection of pharmacological agents and adjuvants, (4) describe potential complications associated with lower extremity nerve blocks, and (5) identify informational gaps pertaining to outcomes, which warrant further investigation.